Identification of the causative mutation in the ITGB2 gene in a LAD1 patient by whole exome sequencing - Kim Lien, Nguyen Thi; Van Anh, Nguyen Thi; Van Tung, Nguyen; Anh Linh, Duong; Phuong Mai, Nguyen Thi; Huy Hoang, Nguyen (Vietnam Journal of Biotechnology, 2022)
Leukocyte adhesion deficiency type 1 (LAD1) is a rare congenital immunodeficiency disease. The cause of disease is determined to be the mutations in the ITGB2 gene that codes for CD18, the beta chain of beta-2 integrins, leads to decreased expression or functioning of CD18. This deficiency leads to severe impairment of leukocyte adhesion to the vascular wall and leukocyte migration to sites of infection and inflammation. LAD1 has also been associated with inhibition of interleukin-23 and interleukin-17 resulting in a hyperinflammatory and chronic inflammation. Patients with LAD1 typically present in early infancy with recurrent, life threatening infections that are frequently fatal before 2 years of age without hematopoietic stem cell transplant (HSCT). However, LAD1 is difficult to diagnose and many LAD1 patients die at a young age despite intensive antibiotic therapy. Accurate diagnosis requires detailed clinical information (delayed umbilical cord loss, severe periodontitis, delayed wound healing and sores, skin abscesses, and recurrent infection), and confirmation the absence of integrins by flow cytometric analysis. A better understanding of the molecular characteristics of this disease is needed to raise awareness and definitive diagnosis infants with LAD1. To definitive diagnosis, whole exome sequencing and Sanger sequencing were performed in an eighteen-month-old boy with severe leukocytosis, recurrent infections, delayed wound healing, and hepatosplenomegaly associated with an acquired cytomegalovirus infection. Two variants: One previously reported mutation (c.533C>T, p.Pro178Leu) and one novel variant (c.59-1G>A), in the ITGB2 gene were detected. These results can be used for definitive genetic diagnosis, genetic counseling, as well as a prenatal diagnosis in LAD1 patients.